Revisiting Pan-Slavism in the Contemporary Perspective. Issue 1 (19th January 2023) - Đorđević, Vladimir; Suslov, Mikhail; Čejka, Marek; Mocek, Ondřej; Hrabálek, Martin
Abstract: In this article, we examine the literature on the topic of Pan-Slavism that has been published in the last 20 years. We do so by paying particular attention to discussions on contemporary perspectives and manifestations of Pan-Slavism that in our view have been largely missing from academic research. We begin the article by introducing a theoretical conceptualization of Pan-Slavism in general, preparing the ground for our inspection of the academic output in the said period. We then continue by presenting our own contribution to the conceptualization and the current state of the field on Pan-Slavism, suggesting venues that future research may take towards broadening the field that has been and remains narrow. We conclude the article by summarizing the key points made therein.